Blended Portland cement with high limestone loads modified with a waste glass based sodium silicate of different ratios SiO2/Na2O. (22nd August 2022) - Santana-Carrillo, Jose Luis; Burciaga-Diaz, Oswaldo; Escalante-Garcia, J. Ivan
Highlights: One-part of portland cement with 60% limestone were modified by a sodium silicate. The sodium silicate was thermochemically synthesized from waste silica soda lime glass. The total added Na2 Oeq (from NaOH) content in the blended cements was kept under 2%. The sodium silicate influenced the early and late properties and reaction products. These low emission binders showed strengths similar to a reference portland cement. Abstract: This paper presents the results of one-part alternative low CO2 cements made of 60%limestone-30% portland cement ((LS-PC)m ) and modified with 10% of a waste glass-based sodium silicate (SWG) synthesized by thermochemically processing blends of waste glass-NaOH of 3 different SiO2 /Na2 O ratios. The added alkali (from NaOH) contents in the (LS-PC)m was kept low, leading to under 2% Na2 Oeq . The reaction products were characterized in pastes and the strength development in mortars. The addition of SWG and its SiO2 /Na2 O ratio had significative effects in the setting time, heat released, flowability, early and late mechanical strength, as well as in the reaction products formed. Lower alkali contents in the SWG did not drastically affect the flowability and setting time, also, the early strength was enhanced without impairing the late strength; in contrast, the opposite occurred for SWG with high alkali contents. The mortars reached acceptable 28-day strengths and similar 180-day strength as a reference Portland cement mortar. The results suggest that the SWG promoted the early formation of carboaluminates and C-S-H of different compositions, evidenced by the signals of six-fold coordinated Al and Q 1, Q 2 (1Al) and Q 2 sites, respectively, in the 27 Al and 29 Si RMN spectra. The studied binders could be a promising alternative, along with other low carbon binders, to contribute to reduce CO2 emissions.